COMPREHENSIBLE INPUT IN LANGUAGE LEARNING - Helena M. Rijoly (Jurusan Pendidikan Bahasa dan Seni FKIP Universitas Pattimura, 2017)
As an instrument of communication, language (language learning) has ignited many thinkers and researchers to explain its phenomena and process. Theories have been developed to explain what is language and all its characteristic and linguistic systems, the theories of language learning and acquisition and the impact of its application in social setting. Acknowledging the significant impact of language use, one may wonder how do we come about to learn language, what triggers it and how can we improve and develop. This paper will reflect upon the role of input and most importantly the comprehensible input in language acquisition and learning (with a nod to several Krashen’sTheories) and put forward some suggestions on how to incorporate comprehensible input in language learning setting